(3TQM eNJUQ GdefJgi dGHf GdMGLHs - (3YVOGdOjf YHO GdQMef Hf CMeO GdEjLis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3eMeO Hf CHh HcQ Gdehdhi GdGQRfLGfi s)
(3ChdgG (B:s
(3hHYO GdYHGO Cf TQY GdCMcGe hHjf GdMdGd hGdMQGe s
(3BNQgG (B:s
(3MUdJ CehQ dGJcGO JMUQ hai GdbOQ GdPi PcQ GQTGO dPdc s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs